THE INTEGRATION OF THE NATIONAL CURRICULUM INTO PESANTREN EDUCATION SYSTEM - Ramli Rasyid (Universitas Islam Negeri Alauddin Makassar, 2012)
the pesantren has been one of the important educational institutions in Indonesia. As an education institution, the curriculum of pesantrens seems to reflect the style and will of the kyai who leads the pesantren, reflect his interpretations of both Islamic traditions, and the changes happening in his society. A pesantren is an indigenous education institution in Indonesia concerned with conducting Islamic education. Kitab kuning teaching is the typical curriculum of pesantren that is applied in the pesantren education system. Some pesantrens still strictly use kitab kuning as their whole curriculum, whereas some others include other curricula into their overall curriculum. Due to globalization and modernity, pesantren - as one of the education system in Indonesia- tries to integrate their curriculum into the national curriculum.